TAXPAYER: E-COMMERCE TAXES DO NOT AFFECT BUYING POWER - Moh. Faisol (LP2M Universitas Bina Mandiri Gorontalo, 2020)
The development of e-commerce in Indonesia is very fast, this is inseparable from the pressures of the 4.0 industrial revolution era, and also the national and global conditions that are overflowing with the Covid 19 pandemic. Along with the development of e-commerce, the government also reaffirms the imposition of taxes (PPN) on The transaction is through PMK 210/2018 and PMK 48/2020, although it is implicitly included in Law Number 36 of 2008. The problem is that the e-commerce tax will affect people's purchasing power because the goods/services being traded are included with PPN by 10%. This study uses an interpretive approach with phenomenological methods. Researchers conducted interviews with thirteen informants, then the results of the interviews were analyzed using qualitative analysis techniques and using NVivo 12 software. The results of this study can provide an understanding that the existence of e-commerce taxes does not affect their purchasing power in making purchases online, because it the main consideration in making e-commerce purchases for them is their need and suitability for these goods. On the other hand, with the e-commerce tax, they realize that the tax paid is an obligation that they must pay, as a form of their participation in the state in the success of the development.